Sex offender registration and community notification laws : an empirical evaluation - Logan, Wayne A., 1960-; Prescott, J. J. (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2021)
Despite being in existence for over a quarter century, costing multiple millions of dollars and affecting the lives of hundreds of thousands of individuals, sex offender registration and notification (SORN) laws have yet to be subject to a book-length treatment of their empirical dimensions - their premises, coverage, and impact on public safety. This volume, edited by Wayne Logan and J.J. Prescott, assembles the leading researchers in the field to provide an in-depth look at what have come to be known as 'Megan's Laws', offering a social science-based analysis of one of the most important, and controversial, criminal justice system initiatives undertaken in modern times.
Origins and evolution / Wayne A. Logan -- Variations in the structure and operation of SORN systems / Andrew J. Harris & Scott M. Walfield -- Registries and registrants : research on the composition of registries / Alissa R. Ackerman -- Law enforcement and SORN / Richard Tewksbury & Kristen Zgoba -- The public and SORN laws / Lisa L. Sample -- The ancillary consequenvces of SORN / Kelly Socia -- Offenders and SORN laws / J.J. Prescott & Amanda Agan -- Integrating the etiology of sexual offending into evidence-based policy and practice / Jill S. Levenson -- Junvenile registration and notification : failed policeis that must end / Elizazeth J. Letourneau.
Title from publisher's bibliographic system (viewed on 11 Jun 2021).
Keywords: Sex offenders -- United States -- Registers; Recording and registration -- United States; Publicity (Law) -- United States; Sex offenders -- Legal status, laws, etc. -- United States